Does One Secure Their Own Salvation? Analysis on Continue to Work Out Your Salvation - Suparyadi, Zakharia; Hariyanto, Hariyanto; Siregar, Sahat; Tumbelaka-Wieland, Josephine Mariana (Sekolah Tinggi Teologi Simpson Ungaran, 2024)
Though conceptually different, Sayyed Hosein Nashr and Hans Kung's ideas on salvation share the same theological characteristics, which includes emphasizing the need of teaching kindness in order to achieve salvation. There is an inconsistency between this concept with the Bible. Luther believed that people are justified by faith and that this is the concept of salvation. What about the advice to